Pengaruh Ice Breaking Berbasis Media Poster Terhadap Minat Belajar Siswa Kelas III - Leny Indriany; Syamsul Alam; Satriawati; Cayati (Jurnal Elementaria Edukasia, 2023)
This is a quantitative research with experimental-type research with pre-experimental form of one graup pretest-posttest design. The research samples were 27 grade IIIB. Data Collection was carried out by observation, questionnaires, and documentation. Data were analyzed by using descriptive and inferential statistical analysis with SPSS version 20 computer program. The resuts indicated that the ability of teachers’ activities by applying poster-based ice breaking abtained an average of 3,4 meaning that it was carried out perfectly. The assessment of student activity in learning obtained average 3.3 with good category. The results of grade IIIB students learning interest were described by the inferential analysis results where the normality test was 0.205, the homogeneity test was 0.219 and the T test was 0.000, so the results indicated that therebis an effect of poster-based ice breaking on grade III students learning interest at Antang I Elementary School, Makassar. Therefore, through the analysis results, it can be concluded that poster-based ice breaking has proven to have an effect on grade III students learning interest of Antang I Elementary School, Makassar. Keywords: poster-based ice breaking, students learning interests